BLOOD PRESSURE PREVALENCE WITH STRATIFICATION AND ASSOCIATIONS: A COMMUNITY-BASED STUDY FROM LONGITUDINAL COHORT HOUSEHOLD SURVEY 2019. (April 2021) - Chakaraborty, Nilanjana; Chakraborty, Kaushik; Mitra, Ramendra Nath; Saha, Angana; Chatterjee, Papri; Manna, Subhankar; Mitra, Dipra
Abstract : Objective: For decades morbidity and mortality due to hypertension remains the major contributor of NCD burden worldwide. Objective is to assess the prevalence of a community cohort's Blood Pressure of all categories: measured hypertension (mHTN), self-reported doctor diagnosed hypertension (DDH), undiagnosed hypertension (UDH), also blood pressure stratification followed as per Joint National Committee-8 guideline. Associations with socio-demographic variables also reported. Aim being to use the study data with collated same cohort's past relevant information as primary tool to formulate burden minimisation intervention protocol of the ongoing population health Study. Design and method: Barrackpore Population Health Study, an urban household-based community cohort of 3030 households commenced in 2001. Third household survey enrolled 6632 participants (Male2576; Female 4056). Beside pre-tested structured questionnaire, real time anthropometric measurements for BMI assessment and Blood Pressure measurement termed as 'Measured Hypertension (mHTN)' also performed in the survey. All measurements were carried out at participants' residence on a working day during working hours according to standard protocol. Results: Among total participants of mHTN (N6632) 31.48% were normotensive, 39.02% were prehypertensive, 20.73% were HTNstg1, 8.76% were HTNstg2. Prevalence of DDH (n = 1563) was 23.57%. Among DDH, prevalence of normotensive 12.35%, well controlled; prehypertensive 37.17%, moderately controlled; HTNstg1 33.21% and HTNstg2 17.27%, both uncontrolled. Undiagnosed HTN (n = 3174) 47.86%. of total population. Among UDH, prehypertensive 63.23%, moderately controlled; HTNstg1 26.97% and HTNstg2 9.79% not controlled. Increasing age was a higher odds of DDH [OR = 1.08, CI: 1.07, 1.10; p < .0001]. Smokers were 27% [OR = 0.73, CI: 0.60, 0.89; P = 0.0019] and alcohol drinkers 47% [OR = 0.53, CI: 0.40, 0.71; p < .0001]. Compare to non-snorers, always snorers were two times [OR = 2.27, CI: 1.93, 2.54; p < .0001] and diabetics were four times [OR = 4.885, CI: 4.20, 5.68; p < .0001] likely to be higher in DDH population. Conclusions: Almost half of the hypertensives remain undiagnosed. Among the diagnosed population, significant majority were not controlled. Association of age, alcohol consumption, smoking, snoring, diabetes and above normal BMI were confirmed. Monitoring of the efficacy of the burden reduction intervention program of the established longitudinal study cohort should be considered.